2015
DOI: 10.20965/jdr.2015.p0363
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Organizational Information Sharing and Coordination in Disaster Response: The Case of the 2008 Wenchuan China Earthquake

Abstract: Information sharing is a vital component of unified planning among multiple agencies performing varied tasks and activities toward effective emergency response, which promotes effective coordination. Insufficient information sharing and ineffective coordination among organizations during a disaster response creates a bottleneck in need of urgent resolution to effect preparedness. Building a highly effective emergency management information system would help to solve this problem. Modern information technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The main advantage of an MTS is to combine expertise to achieve tasks that go beyond the skills of a single sub‐team. Each sub‐team holds information relevant to their own and other teams' behaviour (Abdeen et al, 2021; Strom & Eyerman, 2007; Wang et al, 2015). Yet, ironically, it has been found that sub‐teams working within MTSs tend to prioritize intra‐team over inter‐team communications (Allen et al, 2014; Wang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantage of an MTS is to combine expertise to achieve tasks that go beyond the skills of a single sub‐team. Each sub‐team holds information relevant to their own and other teams' behaviour (Abdeen et al, 2021; Strom & Eyerman, 2007; Wang et al, 2015). Yet, ironically, it has been found that sub‐teams working within MTSs tend to prioritize intra‐team over inter‐team communications (Allen et al, 2014; Wang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Each sub‐team holds information relevant to their own and other teams' behaviour (Abdeen et al, 2021; Strom & Eyerman, 2007; Wang et al, 2015). Yet, ironically, it has been found that sub‐teams working within MTSs tend to prioritize intra‐team over inter‐team communications (Allen et al, 2014; Wang et al, 2015). This tendency to favour intra‐team communications is more likely to happen when under stress (Campbell et al, 2022) and when organizations lack a culture of information sharing (Bharosa et al, 2010; Kwon et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, confusion about the "Operation Plato" declaration and its meaning at the Manchester attack 63 . • Sub-teams working within an MTS tend to prioritise communications with their own sub-team members over communications with other component teams 2,72 which is more likely to happen when under stress 8 . • Teams have been found to lack a culture of information sharing outside of their own organisation 5 .…”
Section: Communication and Information Sharingmentioning
confidence: 99%